2015
DOI: 10.11152/mu.2013.2066.172.anky
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the renal morphology and vascular resistance in patients with ankylosing spondylitis.

Abstract: Aims: To evaluate renal morphology, prevalence of urinary stone disease, renal perfusion and resistance to renal blood flow in patients with ankylosing spondylitis(AS). Material and methods: Thirty-eight patients diagnosed with AS and with normal basal renal functions, together with 38 healthy individuals matched in terms of age, sex, blood lipid profile and body mass index, were included. Total cholesterol, triglyceride, urea, creatinine and glucose levels were measured in both groups, as well as vitamin D, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although of unknown etiology, the formation of calculi requires a complex integration of numerous factors. Resorlu et al reported that 80%-90% of the renal calculi in patients with AS were calcium-based calculi supporting the possibility of problem primarily due to calcium metabolism [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although of unknown etiology, the formation of calculi requires a complex integration of numerous factors. Resorlu et al reported that 80%-90% of the renal calculi in patients with AS were calcium-based calculi supporting the possibility of problem primarily due to calcium metabolism [10].…”
Section: Discussionmentioning
confidence: 99%
“…An extra-articular involvement is common in inflammatory diseases. Although renal involvement has been shown in many studies on AS, the number of studies investigating the coexistence of renal calculi in AS is very limited [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found the unadjusted hazard ratio of urolithiasis for AS compared to the healthy population of 2.4 (95% CI 2.1-2.9). 11 In Turkey in 2015, Resorlu et al 12 detected urolithiasis in 18.4% of AS patients and 10.4% of controls. Eliah et al 13 claimed that limited spinal mobility and pyelo-pelvic position in AS patients might be an underlying predisposing factor for urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2015 study from Turkey, Resorlu et al compared 38 AS patients and 38 healthy controls in terms of frequency of kidney stone. They found urolithiasis was present among 18.4% of AS patients and 10.4% of controls [17].…”
Section: The Evidence For Urolithiasis In Ankylosing Spondylitismentioning
confidence: 95%